Natural inhibitors: A sustainable way to combat aflatoxins - Malik M. Ahmad; Firdaus Qamar; Monica Saifi; Malik Zainul Abdin (Frontiers in Microbiology, 2022)
Among a few hundred mycotoxins, aflatoxins had always posed a major threat to the world. Apart from A. flavus, A. parasiticus, and A. nomius of Aspergillus genus, which are most toxin-producing strains, several fungal bodies including Fusarium, Penicillium, and Alternaria that can biosynthesis aflatoxins. Basically, there are four different types of aflatoxins (Aflatoxin B1 (AFB1), Aflatoxin B2 (AFB2), Aflatoxin G1 (AFG1), Aflatoxin G2 (AFG2)) are produced as secondary metabolites. There are certainly other types of aflatoxins found but they are the by-products of these toxins. The fungal agents generally infect the food crops during harvesting, storing, and/or transporting; making a heavy post-harvest as well as economic loss in both developed and developing countries. And while ingesting the crop products, these toxins get into the dietary system causing aflatoxicosis, liver cirrhosis, etc. Therefore, it is imperative to search for certain ways to control the spread of infections and/or production of these toxins which may also not harm the crop harvest. In this review, we are going to discuss some sustainable methods that can effectively control the spread of infection and inhibit the biosynthesis of aflatoxins.